2017
DOI: 10.1038/s41467-017-02277-7
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Yu-Shiba-Rusinov energies in the weak-coupling Kondo regime

Abstract: The competition of the free-spin state of a paramagnetic impurity on a superconductor with its screened counterpart is characterized by the energy scale of Kondo screening compared to the superconducting pairing energy Δ. When the experimental temperature suppresses Kondo screening, but preserves superconductivity, i.e., when Δ/k B > T > T K (k B is Boltzmann’s constant and T K the Kondo temperature), this description fails. Here, we explore this temperature range in a set of manganese phthalocyanine molecules… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 40 publications
(54 reference statements)
3
57
0
Order By: Relevance
“…3,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The bulk of recent experimental work on YSR states on superconducting (SC) substrates has demonstrated that the strength of the exchange interaction J can be significantly influenced by a small change in the adsorption site of the impurity or by spacers between the impurity and substrate. 3,18,[25][26][27][28][29][30][31][32][33][34] with α proportional to J, α = πρJS/2, where ρ is the normal-state density of states of the substrate at the Fermi level and S is the impurity spin. The bound state results from the spin-dependent scattering of Bogoliubov quasiparticles on the impurity and is thus associ-ated with the longitudinal part of the exchange interaction, JS z s z , where s represents the spin-density of the substrate electrons at the impurity position.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The bulk of recent experimental work on YSR states on superconducting (SC) substrates has demonstrated that the strength of the exchange interaction J can be significantly influenced by a small change in the adsorption site of the impurity or by spacers between the impurity and substrate. 3,18,[25][26][27][28][29][30][31][32][33][34] with α proportional to J, α = πρJS/2, where ρ is the normal-state density of states of the substrate at the Fermi level and S is the impurity spin. The bound state results from the spin-dependent scattering of Bogoliubov quasiparticles on the impurity and is thus associ-ated with the longitudinal part of the exchange interaction, JS z s z , where s represents the spin-density of the substrate electrons at the impurity position.…”
mentioning
confidence: 99%
“…Fitting the data with a phenomenological spin Hamiltonian The exchange coupling between the magnetic impurity and the substrate can be modulated by changing the adsorption site of the molecule. 3,18,[30][31][32]51,52 We successfully posi- Due to the sensitivity of the YSR states and spin-excitations, they can be tuned continuously by the force exerted by the STM tip. 33,34,53 We expect to have attractive forces between the tip and the molecule; 54,55 this would result in pulling the molecule away from the substrate and reduction of the exchange coupling between the molecule and the substrate upon decreasing tip-molecule distance.…”
mentioning
confidence: 99%
“…Recently, theoretical predictions and experimental indications of topological superconductivity in one- [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and two-dimensional [16][17][18][19][20] arrays of magnetic atoms coupled to bulk superconductors have triggered renewed interest in the building blocks of such systems, i.e. single magnetic atoms coupled to bulk superconductors [21][22][23][24][25][26][27][28][29][30] . Magnetic atoms locally induce pairs of bound state resonances inside the gap of their host superconductor, known as Yu-Shiba-Rusinov (YSR) states [31][32][33][34][35] .…”
mentioning
confidence: 99%
“…Upon introducing impurities into graphene, various in-gap states can emerge, manifesting whether it is in the topologically trivial or non-trivial phase 10 . In what follows we study the subgap states of a single impurity existing in the proximitized periodic honeycomb lattice, that have received a great deal of interest both in experimental [11][12][13][14][15] and theoretical studies [16][17][18] . In particular, more complex nanostructures embedded into such proximitized QSHI material could develop the Majorana-type quasiparticles 19 .…”
Section: Introductionmentioning
confidence: 99%